Prevalence of depression, anxiety and stress among obese patients with chronic medical illness in Klinik Rawatan Keluarga, Hospital USM and its associated factors - Hassan, Raihan (2016)
Introduction: Obesity and depression are two prevalent disorders that are costly to both individuals and society especially in patients with chronic medical illness. Depression usually co-exists with anxiety and stress. The aim of this study is to determine the prevalence and the factors associated with depression, anxiety and stress in obese patients with chronic medical illness attending Klinik Rawatan Keluarga. Methods: The study was cross sectional in design and was carried out in HUSM. A total of 274 eligible consenting respondents participated in the study. The Depression, Anxiety and Stress Scale (DASS21) questionnaire was used for measurement of depression, anxiety and stress among the respondents. Data was analysed using the SPSS version 21 software using both descriptive and inferential statistics (single and multiple logistic regression). Results: The prevalence of depression, anxiety and stress among obese patients with chronic medical illness were 13.9%, 23.4%, and 10.9% respectively. Using multiple logistic regression, age (p=0.003, OR: 0.96, 95%CI: 0.91,0.98), occupation (not working)( p=0.013 , OR:3.65 ,95% CI:1.32,10.09,) and current smoker (p=0.022, OR:3.18, 95% CI:1.18,8.55) were associated with depression. For anxiety, the associated factors were no formal education ( p=0.011, OR:5.70, 95%CI: 1.49, 21.89,), BMI (p=0.029, OR:1.07, 95% CI:1.01,1.13) and family history of mental illness (p= 0.018, OR:5.10 ,95% CI: 1.33, 19.56). Stress wasstrongly associated with female gender (OR 5.06, 95% CI 1.70-15.13) and current smoking status (OR 6.49, 95% CI 2.03-20.70).Conclusion: Prevalence of depression, anxiety and stress symptoms in obese patients with chronic medical illness were 13.9%, 23.4% and 10.9% respectively. The significant associated factors were age, not working, BMI, current smoker, no education, family history of mental illness and gender. Screening of obese patients with chronic illness for depression, anxiety and stress at primary care setting is recommended hence early intervention can be offered.